Diversity of Rhizospheric Bacterial Community from Kaolin Mining Site and Their Potential as Plant Growth Promoting Bacteria - Armanisa, Khafifah; Rusmana, Iman; Astuti, Rika Indri (HAYATI Journal of Biosciences, 2025)
Tailing from mining activities affects soil fertility resulting in poor soil conditions that are challenging for plants to grow. Plants can interact with rhizosphere bacteria to enhance their growth in harsh environments. Rhizospheric bacteria possess numerous mechanisms that promote plant growth and induced resistance to various abiotic stress. This study aims to determine the diversity of rhizobacteria and their potential as plant growth-promoting rhizobacteria (PGPR) agents. Bacterial communities from rhizosphere soil samples from kaolin mining sites in Perawas, Tanjung Pandan district, Belitung Regency, Bangka Belitung Island, Indonesia were analyzed using Next Generation Sequencing based on the V3-V4 region of the 16S rRNA gene, while culturable bacteria were isolated from samples and screened for PGP activity. The results showed that the rhizosphere bacterial community was mostly dominated by Pseudomonadota, Acidobacteria, and Verrumicrobiota. There were 15 bacteria isolated from the sample and RKB-5 bacterial isolate had the potential to be PGP agent. The RKB-5 bacterial isolate was identified as Burkholderia cenocepacia based on its 16S rRNA sequence. The bacterial isolate produced IAA, utilized ACC, dissolved phosphate up to 209,5 mg/L, and formed a high potassium solubilizer index value of 5.00. Therefore, the B. cenocepacia RKB-5 has potential application as the PGPR to support plants growth by obtaining nutrients in ex-mining lands with poor soil conditions.